Conflict among experts in health recommendations and corresponding public trust in health experts - Mainous, Arch G.; Sharma, Pooja; Yin, Lu; Wang, Ting; Johannes, Bobbie L.; Harrell, Grant (Frontiers in Medicine, 2024)
Importance Public trust in health experts has been decreasing leading to decreased adherence to expert recommendations.Objective To evaluate public perceptions of conflict and uncertainty among experts in healthcare recommendations and association with decreased trust in health entities for accurate health information.Methods Analysis of the US nationally representative Health Information National Trends Survey (HINTS 6-2022). Adults aged 18 and older were respondents to the survey (unweighted n=5842, representing 241 million adults). The main outcome was trust in doctors, scientists and government health agencies for health information. Analyses examined trust in experts with public perceptions of conflict about recommendations and changing recommendations.There was high trust in doctors for health information (95%) versus 84% in scientists and 70% in government health agencies. Only 18% have high trust in the health information on social media. Respondents who felt expert recommendations change often were less likely to have high trust (65%) in government agencies compared to those who felt that the recommendations didn't often change (82%) (p<.01). In logistic regressions controlling for age, sex, race, education, income and trust in social media for health information perceptions of low conflict among expert health recommendations is associated with likelihood of high trust in government health agencies (OR 2.86; 95% CI 1.96–4.15).The public has low trust in government health agencies and perceptions of conflict among experts over recommendations is likely playing a role in the erosion of trust in health experts.